A preliminary comparison between local public health units in the Canadian Province of Ontario and in the United States. - Schade, Charles P. (Public Health Reports)
Public health departments in the U.S. and in Ontario, Canada, were compared to address the funding and staffing and the size and program content of local health departments after Canada adapted universal, comprehensive publicly funded health insurance in 1971. In Ontario, local health departments are required to provide a uniform set of public health services. In the U.S., the kinds and amounts of services provided vary substantially between jurisdictions. Staff sizes and budget levels in the health units of both Ontario and the U.S. increase in proportion to population served, but per capita expenditures increase only in Ontario when populations decrease. Lack of critical staff or elimination of key programs in small departments in the U.S. can explain this anomaly, and the medical care of indigents is probably the reason for the increased per capita costs seen in very large U.S. health departments. For all jurisdictions in the U.S. to meet the uniform public health services required in Ontario in 1989, $5.8 billion per annum would be necessary.